2015
DOI: 10.1371/journal.pone.0144708
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Scale Genomic, Transcriptomic and Proteomic Analysis of Colorectal Cancer Cell Lines to Identify Novel Biomarkers

Abstract: Selecting colorectal cancer (CRC) patients likely to respond to therapy remains a clinical challenge. The objectives of this study were to establish which genes were differentially expressed with respect to treatment sensitivity and relate this to copy number in a panel of 15 CRC cell lines. Copy number variations of the identified genes were assessed in a cohort of CRCs. IC50’s were measured for 5-fluorouracil, oxaliplatin, and BEZ-235, a PI3K/mTOR inhibitor. Cell lines were profiled using array comparative g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 98 publications
0
34
0
Order By: Relevance
“…UBE2O is localized in the 17q25 locus, the amplification of which is recurrent in a subset of human cancers (Briffa et al, 2015; Lin et al, 2006; Rice et al, 2011; Toffoli et al, 2014; Wang et al, 2015), and we found that in TCGA datasets from cBioPortal (www.cbioportal.org) UBE2O is upregulated in ~20% of human breast, bladder, liver and lung carcinomas (Figures 7A and 7B and Figures S7A and S7B). Previously published microarray-based gene expression analyses have also indicated a high expression rate of UBE2O in several subsets of human cancer (Figure 7C and Figure S7C).…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…UBE2O is localized in the 17q25 locus, the amplification of which is recurrent in a subset of human cancers (Briffa et al, 2015; Lin et al, 2006; Rice et al, 2011; Toffoli et al, 2014; Wang et al, 2015), and we found that in TCGA datasets from cBioPortal (www.cbioportal.org) UBE2O is upregulated in ~20% of human breast, bladder, liver and lung carcinomas (Figures 7A and 7B and Figures S7A and S7B). Previously published microarray-based gene expression analyses have also indicated a high expression rate of UBE2O in several subsets of human cancer (Figure 7C and Figure S7C).…”
Section: Resultsmentioning
confidence: 78%
“…However, in vivo evaluation of UBE2O has been limited by a lack of appropriate animal models. Intriguingly, UBE2O is localized in the 17q25 chromosome region, which is amplified in a subset of human cancers (Briffa et al, 2015; Lin et al, 2006; Rice et al, 2011; Toffoli et al, 2014; Wang et al, 2015), but its role in tumorigenesis has yet to be fully described.…”
Section: Introductionmentioning
confidence: 99%
“…Our data demonstrate what we believe to be a previously unrecognized role for the ubiquitin-conjugating enzyme UBE2O in the regulation of energy homeostasis and insulin sensitivity in vivo. Whereas UBE2O is known to be recurrently amplified in human cancers (38)(39)(40)(41)(42), we have now shown that UBE2O is universally upregulated in animal models exhibiting insulin resistance and metabolic disorders. Whole-body knockout of Ube2o in mice reverses the gains in weight, white fat mass, and body lipid content resulting from overnutrition.…”
Section: Discussionmentioning
confidence: 75%
“…These previous reports support our results. Although the participation of other putative oncogenes involved in the sensitivity to irinotecan or resistance to oxaliplatin, such as TRIB1 [21] and POU5F1B [22], which are chromosomally located near MYC, cannot be excluded, we hypothesize that MYC is the most promising positive predictive biomarker. Further validation and functional studies from a viewpoint of chemosensitivity are required to determine the potential roles of these genes in patients with mCRC.…”
Section: Discussionmentioning
confidence: 88%